2023
DOI: 10.1111/ene.15696
|View full text |Cite
|
Sign up to set email alerts
|

Sexual dysfunction in female and male people with multiple sclerosis: disability, depression and hormonal status matter

Abstract: Background and purpose Sexual dysfunction (SD) in people with multiple sclerosis (pwMS) is common and an often underestimated issue in the care of pwMS. The objective of the study was to evaluate risk factors for SD in pwMS, correlate its prevalence with patient‐reported measures (quality of life and physical activity) and analyse its association with hormonal status. Methods Sexual dysfunction was determined in 152 pwMS using the Multiple Sclerosis Intimacy and Sexuality Questionnaire 19. A logistical regress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…Most studies used standardized questionnaires such as MS Quality of Life [ 26 , 30 , 36 38 ], MS Intimacy and Sexuality Questionnaire [ 29 , 35 , 39 46 ], Sexual Quality of Life Questionnaire for men [ 35 , 44 , 47 , 48 ], and International Index of Erectile Function [ 44 , 47 , 48 ], but other methods also included original surveys created by the investigators [ 46 , 49 ], or other validated forms [ 38 , 39 , 46 , 49 51 ]. Serum laboratory tests [ 42 ] and magnetic resonance imaging (MRI) [ 35 ] were uncommon across studies. Based on instruments applied, sexual dysfunction was predominantly determined as a composite qualitative outcome comprising a sexual quality of life metric in combination with measurements of erectile dysfunction and issues with libido, orgasm, or ejaculation.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Most studies used standardized questionnaires such as MS Quality of Life [ 26 , 30 , 36 38 ], MS Intimacy and Sexuality Questionnaire [ 29 , 35 , 39 46 ], Sexual Quality of Life Questionnaire for men [ 35 , 44 , 47 , 48 ], and International Index of Erectile Function [ 44 , 47 , 48 ], but other methods also included original surveys created by the investigators [ 46 , 49 ], or other validated forms [ 38 , 39 , 46 , 49 51 ]. Serum laboratory tests [ 42 ] and magnetic resonance imaging (MRI) [ 35 ] were uncommon across studies. Based on instruments applied, sexual dysfunction was predominantly determined as a composite qualitative outcome comprising a sexual quality of life metric in combination with measurements of erectile dysfunction and issues with libido, orgasm, or ejaculation.…”
Section: Resultsmentioning
confidence: 99%
“…In the same study, 6/20 MwMS reported that other MS symptoms overshadow their sexual problems, and 5/20 felt there was insufficient time to discuss sexual function during the encounter [ 46 ]. In a cross-sectional study of 50 MwMS investigating serum sex hormone profiles including 17-beta estradiol, progesterone, androstenedione, dehydroepiandrosterone-sulfate, total testosterone, estrone, prolactin, sex hormone-binding globulin, inhibin B, and anti-Mullerian hormone, there were no substantial differences in those with or without sexual dysfunction, except for lower levels of inhibin B in those with sexual dysfunction [ 42 ]. No specific brain or spinal cord MRI findings were found to be associated with the severity of sexual dysfunction [ 35 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…42 Multiple sclerosis and spinal cord injuries are examples of conditions that disrupt the nerves that govern ejaculation. 43 PE may be genetically predisposed in some males. The polymorphism in the serotonin transporter-linked polymorphic region (5-HTTLPR) gene has been the subject of the most research (11 studies), with 7 demonstrating a significant association with PE and 4 refuting such a relationship.…”
Section: Reproductive Disorders In Menmentioning
confidence: 99%